Arlo Smith for Attorney General Press Conference - Watkins, Howard::::::::: (1989)
Seated: Don Fischbach, Howard Watkins speaking, Judy Soley and ?; Standing Hmong Community representatives; Arlo Smith, Mike Idiart, ?, ?, ? and Tom Bohigian